PENGARUH MOTIVASI BELAJAR MAHASISWA DAN KOMPETENSI DOSEN TERHADAP PRESTASI BELAJAR - Mediawati, Elis (Dinamika Pendidikan, 2010)
The high or low studentsâ achievement in teaching and learning activities is mainly influenced by factors which are inside the students themselves (internal factors) and factors which are outside the students (external factors). In this study, there was one element of each factors above which would be studied; the internal factor was studentsâ motivation and the external factor was the teacher competence that influenced the learning outcomes. Studentsâ motivation is important because the students themselves who determine the success of learning. Lecturer competence is also important in learning, because lecturer is someone who is dealing with students directly in teaching and learning activities, so we need lecturers whose high competence to improve the learning achievement. The method used in this research was descriptive method, i.e. the researcher collected and compiled the data, and then it was described and analyzed by using statistical calculations, regression analysis, while the technique of data collection was questionnaire. The result of this study was studentsâ learning motivation and lecturerâs competence have a positive and significant influence either partially or simultaneously to students learning achievement